2019
DOI: 10.3920/bm2018.0163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a probiotic blend on gastrointestinal symptoms in constipated patients: a double blind, randomised, placebo controlled 2-week trial

Abstract: Selected strains of lactobacilli and bifidobacteria are known to ameliorate constipation-related symptoms and have previously shown efficacy on digestive health. In this clinical trial, the safety and effectiveness of a probiotic blend containing lactobacilli and bifidobacteria were evaluated in adults with self-reported bloating and functional constipation. Constipation was diagnosed by the Rome III criteria. A total of 156 adults were randomised into this double-blind and placebo-controlled trial. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
4
12
0
1
Order By: Relevance
“…Therefore, endogenous and consumed bifidobacteria, including B. lactis HN019™, could divert the fermentation in the colon toward non-gaseous end-products. This property of B. lactis HN019™ may support tolerance for the fermentation of oligosaccharides in vivo , which is in line with clinical observations of B. lactis HN019™ on reduced flatulence ( 21 , 32 ). In addition, lactate and acetate are produced during B. lactis HN019™ fermentation, indicating potential roles in digestion of dietary components without differentiation of the origin; carbohydrate or protein ( 89 , 102 ).…”
Section: Assist Digestion and Utilization Of Macronutrientssupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, endogenous and consumed bifidobacteria, including B. lactis HN019™, could divert the fermentation in the colon toward non-gaseous end-products. This property of B. lactis HN019™ may support tolerance for the fermentation of oligosaccharides in vivo , which is in line with clinical observations of B. lactis HN019™ on reduced flatulence ( 21 , 32 ). In addition, lactate and acetate are produced during B. lactis HN019™ fermentation, indicating potential roles in digestion of dietary components without differentiation of the origin; carbohydrate or protein ( 89 , 102 ).…”
Section: Assist Digestion and Utilization Of Macronutrientssupporting
confidence: 84%
“…In Ibarra et al ( 22 ), when comparing the measured gastrointestinal symptoms between subjects taken B. lactis HN019™ vs. placebo, only a reduction observed in the degree of straining in the sub-group of subjects (BMF<3). Improvements of gastrointestinal symptoms were also observed in studies with B. lactis HN019™ in combination with other probiotics or prebiotics ( 21 , 27 ) ( Table 1 ).…”
Section: Regulate Gut Motility and Improve Symptoms In Constipationmentioning
confidence: 73%
“…The low detection of L. acidophilus NCFM is difficult to explain, as earlier studies have reported substantially higher fecal recovery levels: 6.6 and 6.7 Log10 genomes/g feces [12,13]. The number of subjects with detectable probiotics was similar for L. paracasei Lpc-37, B. lactis Bl-04, and B. lactis Bi-07, but was less for L. acidophilus NCFM; this is in line with earlier observations on fecal recovery of these strains in healthy subjects not consuming antibiotics [9].…”
Section: Discussionsupporting
confidence: 89%
“…[ 78 ]. Although individual studies have reported varied efficacies [ 79 , 80 ], an earlier systemic review and meta-analysis of randomized–controlled trials indicated that probiotics may improve the whole-gut transit time, stool frequency, and stool consistency; Bifidobacterium lactis showed better efficacies than Lactobacillus casei Shirota [ 81 ]. A more recent systemic review and meta-analysis arrived at a similar conclusion that probiotics increase stool frequency and decrease intestinal transit time in FC patients [ 82 ].…”
Section: Introductionmentioning
confidence: 99%